1981
DOI: 10.2527/jas1981.52137x
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of Genetic and Environmental Effects on Performance Traits from Limousin Field Data

Abstract: Approximately 197,000 field records frm the North American Limousin Foundation performance testing program provided two major data sets and four subsets by sex for the estimation of variance components and heritabilities. The model included contemporary group, sire, breed composition of dam, age of dam and a covariate for age of calf for some traits. Heritabilities with sexes combined were: birth weight, .16 +/- .02; multiplicative age of dam corrected and age of calf adjusted 205-day weight, .08 +/- .01; age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 0 publications
2
3
0
Order By: Relevance
“…Similar results for birth weight have been described by Sierra [31] in Spanish Brown Swiss cattle before being selected for milk production, Villalba et al [36] in the Brown Swiss and Pirenaica, and Benyshek et al [3] in the Simmental. The increase of birth weight until the dam attains maturity has also been documented in Simmental calves [3], Limousine calves [22], Suffolk lambs [15], and South African Mutton Merino and Dormer lambs [8]. Weaning weight and daily weight gain were comparable with the results obtained in the Spanish Brown Swiss [31], and Brown Swiss and Pirenaica [36].…”
Section: Discussionsupporting
confidence: 64%
“…Similar results for birth weight have been described by Sierra [31] in Spanish Brown Swiss cattle before being selected for milk production, Villalba et al [36] in the Brown Swiss and Pirenaica, and Benyshek et al [3] in the Simmental. The increase of birth weight until the dam attains maturity has also been documented in Simmental calves [3], Limousine calves [22], Suffolk lambs [15], and South African Mutton Merino and Dormer lambs [8]. Weaning weight and daily weight gain were comparable with the results obtained in the Spanish Brown Swiss [31], and Brown Swiss and Pirenaica [36].…”
Section: Discussionsupporting
confidence: 64%
“…These estimates imply that yearling weight was a lowly heritable trait and environment controlled most of the variation. These estimates were similar to those (0.14±0.02) reported by Massey and Benyshek (1981) in Limousin breed. Morris et al (1992) reported 0.17±0.06 as an estimate for yearling weight heritability in Hereford cattle.…”
Section: Yearling Weightsupporting
confidence: 91%
“…Calf birth weight has been shown to be an important factor associated with ease of calving (Bellows et al 1971;Laster et (Massey and Benyshek 1981) and from the American Simmental Association (Burfening et al 1978) (20-35, 36-47, 48*59 and 60-192 Searle (19'71 …”
mentioning
confidence: 99%